2021
DOI: 10.3390/ma14102644
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Contact Deformations in Support Systems Using Roller Prisms

Abstract: This article presents the results of finite element analyses of the influence of reaction forces on stresses and strains at the contact points of the rollers of prism supports with cylindrical surfaces of the main journals of large-sized crankshafts. The analyses of strains and stresses, as well as the depth of their occurrences, in the case of the shaft journal and support rollers were carried out using Hertz contact theory and the finite element method. These calculation results proved to be highly consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The implementation of variable support reaction forces ensures the elimination of the elastic deformation of the crankshafts, which distorts the measurements of the geometric quantities. This fact has also been verified experimentally in previous works [5,26]. As emphasized at the beginning of this paper, observations made during earlier research suggested that the implementation of the variable reaction forces could result in different values of the reaction forces on the rollers of the prism heads that support the crankshaft compliant support system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The implementation of variable support reaction forces ensures the elimination of the elastic deformation of the crankshafts, which distorts the measurements of the geometric quantities. This fact has also been verified experimentally in previous works [5,26]. As emphasized at the beginning of this paper, observations made during earlier research suggested that the implementation of the variable reaction forces could result in different values of the reaction forces on the rollers of the prism heads that support the crankshaft compliant support system.…”
Section: Discussionsupporting
confidence: 79%
“…This specificity results from large dimensions that distinguish them from other crankshafts [1,2]. When characterizing the large-sized crankshafts, it should be emphasized that these are components with large weights and dimensions, and at the same time variable rigidity, which makes them susceptible to bending deformations [3][4][5]. Such crankshafts have small cross-sectional dimensions in relation to their length and a number of additional design details that differ from simple shafts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For the steel balls being used in the DBT, the Young's modulus and Poisson ratio have been given as 210 GPA and 0.28, [20] respectively. If these values are inserted into Equation (7), then the maximum pressures Pmax, for the three ball sizes will be as presented in Table 4 It can be observed that there is an almost perfect linear correlation between the radius and Pmax as shown in Figure 5.…”
Section: Drop Ball Test (Dbt) Resultsmentioning
confidence: 99%
“…Pawełko proposed a finite element modeling method considering the preload force of linear rolling guides and compared the solid modeling method with the spring cell method, which finally verified the superiority of the spring cell method in terms of modeling efficiency and modeling accuracy [7] . Nozdrzykowski analyzed the strains and stresses in the support rollers of a large crankshaft spindle based on finite element modeling and verified experimentally [8] . Dunaj performed a finite element simulation analysis of the linear guide stiffness with preload by changing the rollers to rod elements of equal stiffness [9] .…”
Section: Introductionmentioning
confidence: 99%